Sustainable solid waste management practices in Imbak Canyon Conservation Area (ICCA): an assessment of current practices and opportunities for improvement - Dusim, Haidy Henry; Korom, Alexius; Bagang, Tony Paridi (Faculty of Administrative Science and Policy Studies, 2023)
Malaysia places great importance on conserving biodiversity, as evidenced by the establishment of protected areas and national parks. The country's abundant and unique natural resources, combined with improved tourism services, attract visitors who wish to explore its remarkable landscapes. However, the increasing popularity of ecotourism and recreational activities poses potential threats to these protected areas. Similarly, the Imbak Canyon Conservation Area (ICCA) in Sabah, Malaysia, shares the objective of safeguarding the environment and biodiversity but faces challenges due to the negative impacts of recreational activities, including ecotourism. Therefore, it is crucial to assess sustainable practices for effectively managing solid waste in conservation centres. The rising volume of waste generation in Malaysia raises concerns about solid waste management. To determine the elements of sustainable solid waste management practices specifically within the ICCA, this study uses in-depth interviews and focus group discussions (FGD). Thematic analysis is employed to analyse and interpret the insights derived from these interviews and (FGD). The findings reveal the presence of sustainable solid waste management practices in various stages, including waste generation, storage, collection, transfer, recovery, and disposal within the ICCA. However, significant opportunities for improvement exist in the ICCA's solid waste management practices.